2022
DOI: 10.1039/d2ja00016d
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of limit of detection sensitivities in the parts per billion range using conventional geometry synchrotron radiation excited EDXRF measurements

Abstract: Energy dispersive X-ray fluorescence (EDXRF) is a widely used non-destructive technique for micro and trace multi-element analysis of materials. Conventional trials show that using laboratory assisted EDXRF measurements, one can...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Although TXRF spectrometry is usually considered to be the best XRF method for obtaining excellent low LODs , other geometries such as conventional XRF spectrometry and μXRF spectrometry can be optimised to have an ultra-low background and therefore very low LODs. Alam et al 45 demonstrated that the absolute LODs of a few μg obtained when using a conventional EDXRF geometry could be improved to the levels obtained using TXRF spectrometry by preparing minute amounts (90 ng of a multielement RM) of sample on thin kapton foils (12–100 μm). Both techniques were applied at a synchrotron facility (BL-16 beamline of Indus-2) to make use of the polarisation of the synchrotron light and a geometry with an azimuth angle of 0° and a scattering angle 90°.…”
Section: Grazing X-ray Techniques Including Txrf Spectrometrymentioning
confidence: 99%
“…Although TXRF spectrometry is usually considered to be the best XRF method for obtaining excellent low LODs , other geometries such as conventional XRF spectrometry and μXRF spectrometry can be optimised to have an ultra-low background and therefore very low LODs. Alam et al 45 demonstrated that the absolute LODs of a few μg obtained when using a conventional EDXRF geometry could be improved to the levels obtained using TXRF spectrometry by preparing minute amounts (90 ng of a multielement RM) of sample on thin kapton foils (12–100 μm). Both techniques were applied at a synchrotron facility (BL-16 beamline of Indus-2) to make use of the polarisation of the synchrotron light and a geometry with an azimuth angle of 0° and a scattering angle 90°.…”
Section: Grazing X-ray Techniques Including Txrf Spectrometrymentioning
confidence: 99%